KEEFEKTIFAN MODEL TTW BERBANTUAN MEDIA DIGITAL VEKBAL DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Latif Fatul Tamara; Yuni Ratnasari; Denni Agung Santoso (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2026)
This research study aims to find out how effective the implementation of the TTW model with the help of Vekbal's digital media in improving the ability of students in class V of SDN Mangunrejo 2 in solving problems. This type of research uses a quantitative approach to pre-experimental design, using one group pretest-posttest design. This study used 20 students in class V as a population and was sampled using exhaustive sampling. Data is collected with observation, interviews, documentation, and description questions. Data was analysed with validity test, prerequisite test using normality test and N-Gain statistical test with SPSS 25. The research obtained the results of the N-Gain Score test showed an increase in the student's ability to solve problems with an average score of 0.6525 which is categorised as medium. Meanwhile, N-Gain percent obtained an average of 65,2485 which was interpreted quite effectively. According to the research results, it can be concluded that the use of the TTW model with the help of Vekbal digital media is quite effective in improving the ability of class V students of SDN Mangunrejo 2 in solving mathematical problems.